(untitled) (Journal of Asian Development Studies, 2025)
The present research examines the multifold lived experiences of female doctoral students who took more than five years to complete their degrees at public sector universities in Punjab. It focused on prior life conditions, the motivation behind enrolment, and the academic experience, including departmental support, university policies, and supervisory practices. Along with this, the multifaceted phenomenon of the doctoral journey of females living in a traditional society with multiple gendered roles, social norms, expectations, and stereotypes also unfolded. It reflects the disruptions and barriers inherent in individual nature that affect the entire lived experience. A qualitative, transcendental phenomenological approach was employed as the study design; data were collected from 22 females who had completed their PhDs from public sector universities in Punjab within the last year. The findings of the present study reveal a higher tendency among high achievers to enrol in doctoral degrees; furthermore, it suggests that most females who pursued PhD degrees also experienced marriage, pregnancy, motherhood, and jobs along with their PhD degrees. The academic experience of public sector universities highlights the dire need for well equipped labs, a sufficient number of faculty, and policy implementations for a better academic and supervisory experience. The study also unfolds the individual and dynamic nature of challenges of females as they cope with multiple roles, surrounded by social expectations and stereotypes of gender biases. It suggests the need for policy reforms in structure and implementation, as well as orientations before enrolment, campus facilities for mothers, provision of study leave for working professionals, funding, and promotion of a positive culture of research and innovation.